NILAI-NILAI PENDIDIKAN ISLAM: (Tela’ah Novel Kasidah-Kasidah Cinta) - Nurul Indana; Noor Fatikah; Nady Nady (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Along with development of globalization, literary works also makes an important contribution to education. One of the novels that included Islamic values ??especially in moral messages is the novel "Kasidah-Kasidah Cinta" written Muhammad Muhyidin which is full of knowledge, especially about religious knowledge, so that it feels more alive and real. The Islamic education value is the value of Islam that supports education implementation and even becomes a series or system such values as the value of faith, knowledge, worship morals, and the value of struggle. Meanwhile the value of education in the Kasidah-Kasidah Cinta novel is about faith, worship and morals education.Along with development of globalization, literary works also makes an important contribution to education. One of the novels that included Islamic values ??especially in moral messages is the novel "Kasidah-Kasidah Cinta" written Muhammad Muhyidin which is full of knowledge, especially about religious knowledge, so that it feels more alive and real. The Islamic education value is the value of Islam that supports education implementation and even becomes a series or system such values as the value of faith, knowledge, worship morals, and the value of struggle. Meanwhile the value of education in the Kasidah-Kasidah Cinta novel is about faith, worship and morals education.